2016
DOI: 10.1094/pdis-04-15-0487-re
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Affects Aggressiveness and Fungicide Sensitivity of Four Pythium spp. that Cause Soybean and Corn Damping Off in Iowa

Abstract: Damping off of soybean and corn, caused by Pythium spp., is favored by cool temperatures and wet soil conditions and is primarily managed using fungicide seed treatments. The goal of this research was to determine the effect of temperature on aggressiveness and fungicide sensitivity of Pythium spp. recovered from soybean and corn in Iowa. A total of 21 isolates of four of the most prevalent Pythium spp. in Iowa were screened. Seed and seedling assays were used to quantify the aggressiveness of P. lutarium, P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 48 publications
7
53
0
1
Order By: Relevance
“…that were recovered from rye roots in the field were capable of causing seedling disease of corn in controlled-environment studies. These four species also had been previously identified as causing seedling disease of corn in fields without cover crops (Matthiesen et al 2016;Munkvold and O'Mara 2002). Thus, we suggest that a rye cover crop may serve as a green bridge for corn pathogens, and that emerging corn seedlings following a rye cover crop may be exposed to higherthan-normal pathogen inoculum densities.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…that were recovered from rye roots in the field were capable of causing seedling disease of corn in controlled-environment studies. These four species also had been previously identified as causing seedling disease of corn in fields without cover crops (Matthiesen et al 2016;Munkvold and O'Mara 2002). Thus, we suggest that a rye cover crop may serve as a green bridge for corn pathogens, and that emerging corn seedlings following a rye cover crop may be exposed to higherthan-normal pathogen inoculum densities.…”
supporting
confidence: 54%
“…The tissue pieces were placed underneath an agar medium. For isolation of oomycetes such as Pythium spp., corn meal agar containing pimaricin (5 mg/ml), ampicillin (250 mg/ml), rifampicin (10 mg/ml), pentachloronitrobenzene (50 mg/ml), and benomyl (10 mg/ml) (PARP+B medium) was used (Matthiesen et al 2016). For isolation of fungi such as Fusarium spp.…”
Section: Methodsmentioning
confidence: 99%
“…HSPs were previously characterized as signal transductors in stress‐related responses . In the case of reduced pesticide toxicity in A. arabiensis due to elevated temperature, authors suggested that this response was mediated by the activity of HSPs and several related genes were found to be upregulated under the combination of elevated temperature and avermectin (insecticide) treatment . HSPs were also found to play a role in the opposite case of enhanced pesticide toxicity under a combination of high temperatures and avermectin treatment in Frankliniella occidentalis .…”
Section: What Is the Mechanism Underlying Conditional Resistance?mentioning
confidence: 99%
“…Pythium sylvaticum fungicide sensitivity was reduced under elevated temperature whereas the opposite trend was observed in P. torulosum. 15 In Anopheles arabiensis, increasing the temperature reduced pyrethroid sensitivity. 16 In the brown plant hopper Nilaparvata lugens, a serious rice (Oryza sativa) pest in Asia, the sensitivity of the pest to triazophos was significantly decreased in enriched, compared to ambient, CO 2 levels.…”
Section: Conditional Resistancementioning
confidence: 99%
“…For example, Broders et al (2007aBroders et al ( , 2007b recovered nine species of Pythium and eight species of Fusarium from diseased corn seedlings in Ohio. Similarly, Matthiesen et al (2016) recovered nine species of Pythium from diseased corn seedlings in Iowa and in a few cases recovered multiple species from individual plants. The presence of multiple species and genera capable of infecting corn seedlings within a field undoubtedly complicates development of effective disease management strategies.…”
Section: Introductionmentioning
confidence: 99%